Bill Monroe : the life and music of the Blue Grass man - Ewing, Tom, 1946- (Music in American life., 2018)
"The Father of Bluegrass Music, Bill Monroe was a major star of the Grand Ole Opry for over fifty years; a member of the Country Music, Songwriters, and Rock and Roll Halls of Fame; and a legendary figure in American music. This authoritative biography sets out to examine his life in careful detail--to move beyond hearsay and sensationalism to explain how and why he accomplished so much. Former Blue Grass Boy and longtime music journalist Tom Ewing draws on hundreds of interviews, his personal relationship with Monroe, and an immense personal archive of materials to separate the truth from longstanding myth. Ewing tells the story of the Monroe family's musical household and Bill's early career in the Monroe Brothers duo. He brings to life Monroe's 1940s heyday with the Classic Bluegrass Band, the renewed fervor for his music sparked by the folk revival of the 1960s, and his declining fortunes in the years that followed. Throughout, Ewing deftly captures Monroe's relationships and the personalities of an ever-shifting roster of band members while shedding light on his business dealings and his pioneering work with Bean Blossom and other music festivals. Filled with a wealth of previously unknown details, Bill Monroe offers even the most devoted fan a deeper understanding of Monroe's towering achievements and timeless music"--Inside dust jacket.